Smoothed Particle Hydrodynamics multiphase modelling of an experimental microfluidic device for conformal coating of pancreatic islets. (March 2020) - Sibilla, Stefano; Manenti, Sauro; Cazzato, Tommaso; Colombo, Federica; Tomei, Alice A.; Redaelli, Alberto; Manzoli, Vita; Consolo, Filippo
Highlights: SPH model of the flow in a device for pancreatic islets conformal coating. Encapsulation process suitably reproduced while assuring phase conservation. Simulation of jet fragmentation and surface tension effects on islet coating process. Evaluation of influence of process parameters on the shape of encapsulated islets. Abstract: The paper discusses a Smoothed Particle Hydrodynamics (SPH) model for the analysis of the multiphase flow occurring in an experimental microfluidic device for conformal coating of pancreatic islets with a biocompatible and permeable polymer. The proposed numerical model, based on a weakly-compressible SPH approach, accurately mimics the encapsulation process while assuring phase conservation, thus overcoming potential limitations of grid-based models. The proposed SPH model is a triphasic multi-phase model that allows one: (i) to reproduce the physics of islet conformal coating, including the effects of surface tension at the interface of the involved fluids and of the islet diameter; and (ii) to evaluate how modulation of process parameters influences the fluid dynamics within the microfluidic device and the resulting coating characteristics. This model can represent a valuable, time- and cost-effective tool for the definition of optimized encapsulation conditions through in silico screening of novel combinations of conformal coating parameters, including polymeric coating blends, size range of insulin-secreting cell clusters, utilized chemical reagents, device geometry and scale.